Instalasi Gama Rain Filter Dalam Meningkatkan Akses Air Bersih Pada Masyarakat Pedesaan (Studi Kasus Pada PT Wujudkan Mandiri Air) - Labibah Izzati Firdaus; Lia Nirawati (International Forum of Researchers and Lecturers, 2023)
Indonesia is a country that has potential water resources due to high rainfall but is very vulnerable to water crises. This fact shows the great urgency of the need for clean water. One effective solution to deal with this is through the use of rainwater. Harvesting rainwater is an effective step because Indonesia itself has high rainfall so that during the rainy season the product from PT Wujudkan, namely Gama Rain Filter, will collect water and in the dry season it will be used for daily needs. The purpose of this study is to find out about the implementation of the gamma rain filter in increasing access to clean water in rural communities. The research method used is a qualitative approach to gain a deep understanding of the effect of the Gama Rain Filter installation in increasing access to clean water in rural communities. The findings of this study are that with this superior technology, Gama Rain Filter helps people save water resources for drinking purposes during the rainy season. Therefore, existing funds can be used to obtain food sources that contain lots of protein